A review of agricultural, food security, food systems and climate change adaptation policies, institutions and actors in East Africa - Nzuma, J.M.; Radeny, Maren A.O.; Kinyangi, James; Cramer, Laura K. (2014)
Agricultural production systems in East Africa are mainly rain-fed and highly vulnerable to climate change and variability. Moreover, the smallholder subsistence production base increases the vulnerability of the agricultural sector in East Africa to climate risks. The frequency and severity of climate shocks such as drought, heat and cold stress as well as floods are increasing and likely to lead to major food crises. Governmental and nongovernmental actors in East African countries have instituted policies and programs aimed at increasing agricultural productivity, improving food security and enhancing adaptation to climate change. This paper examines the various policies, institutions and actors related to climate change adaptation, food security, food system and agricultural development in East Africa—focusing on Ethiopia, Kenya, Tanzania and Uganda. The paper combines a review of literature with key informant interviews from various actors in the four countries.